Phialophora section Catenulatae disassembled: New genera, species, and combinations and a new family encompassing taxa with cleistothecial ascomata and phialidic asexual states - Untereiner, Wendy A; Yue, Qun; Chen, Li; Li, Yan; Bills, Gerald F; Štěpánek, Václav; Réblová, Martina (Mycologia, 2019)
The Pleuroascaceae (Leotiomycetes) is introduced for Phialophora hyalina (section Catenulatae) and its closest relatives based on analyses of DNA sequences of five gene regions and the comparison of cultural and micromorphological characters. The family is resolved as a strongly supported clade that encompasses Pleuroascus and the new anamorph genera Entimomentora and Venustampulla. The latter includes V. parva, a species placed formerly in Scopulariopsis, and V. echinocandica, which is established for the echinocandin-producing isolate BP-5553. Entimomentora includes E. hyalina, a species based on the ex-type strain of Ph. hyalina. Additional isolates identified as Ph. hyalina are distantly related to the Pleuroacaceae and include Psychrophila antarctica (Arachnopezizaceae) and Cryonesomyces dreyfussii, the sole member of the new genus Cryonesomyces (incertae sedis). Isolates identified or deposited as Ph. alba are also not closely related; they include a species for which we propose the name Neobulgaria koningiana (Gelatinodiscaceae) and a second psychrophilic species that we describe as Psychrophila lagodekhiensis. Of the 13 isolates assessed for in vitro antifungal activity, only V. echinocandica inhibited the growth of Candida albicans.
Keywords: Antifungal Agents; RNA, Fungal; DNA, Fungal; Cluster Analysis; Anamorph; RNA-polymerasa II; Phialophora; fylogeneze; RNA, Ribosomal, 18S; vysokoúčinná kapalinová chromatografie; Sequence Analysis, DNA; RNA Polymerase II; Phylogeny; ribozomální DNA; sekvenční analýza DNA; antifungální látky; Microbial Sensitivity Tests; shluková analýza; Microscopy; systematics; Mass Spectrometry; fungální RNA; Chromatography, High Pressure Liquid; DNA fungální; echinocandin; RNA ribozomální 28S; geny rRNA; Genes, rRNA; mikroskopie; mikrobiální testy citlivosti; mikrobiologické techniky; hmotnostní spektrometrie; DNA, Ribosomal; RNA ribozomální 18S; Microbiological Techniques; phylogeny; RNA, Ribosomal, 28S; 10 new taxa